Penerapan Metode Perbandingan Eksponensial dalam Menentukan Kinerja Perangkat Desa - Sari, Fatimah Rama; Ramdhan , William; Dermawan , Ari (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Village apparatus is an important thing in the village for serving the community. However, carrying out the assessment process takes a long time and also requires determining which village officials are worthy of being given the best village officials. The aim of this research is to build a decision support system by applying the MPE method to determine the assessment of village officials. The model used to build this system is the Software Development Life Cycle with stages of planning, analysis, design, implementation, testing and management. This research was carried out at the Prapat Janji Village Office. The planning stage is carried out to obtain a performance assessment plan for village officials. Next, the analysis stage was carried out to obtain the system requirements that we developed using the MPE method. Next, the coding and testing stages carried out system creation and testing using a black box. The results of our findings are in the form of a decision support system to determine the best assessment of village officials. The test results show that this system is running well, and is in accordance with the design and model implemented. With this system, it can help the village in determining whether or not village officials will be given rewards.